Pablo de Santa María and Jerónimo de Santa Fe : rereading Lorqi's Epistle (Estudios de Historia de España, 2017)
The conversion of the Jews to Christianity in Spain in the 1391-1492 period goes beyond the demographic question. It has given rise to a broad historiographic corpus and discussion. A central piece of evidence in it has been the Hebrew Epistle of Yehoshua Ha-Lorqi, later known as Jeronimo de Santa Fe. The article attends, firstly, to neglected aspects such as formal qualities, rhetoric, topoi, communicability, stylistics. It then proceeds to note some affinities between the writings of Shlomo/Yehoshua and those of Shlomo’s son: Alonso de Cartagena
Keywords: Conversos; Epistolography; Judeo-Christian Polemics; Alonso de Cartagena; Pablo de Burgos; Jeronimo de Santa Fe